Early Clinical Outcomes of Durvalumab Plus Tremelimumab in Unresectable Hepatocellular Carcinoma: A Real-World Comparison with First-Line or Later-Line Treatment - Yudai Fujiwara; Hidekatsu Kuroda; Tamami Abe; Keisuke Kakisaka; Ippeki Nakaya; Asami Ito; Takuya Watanabe; Kenji Yusa; Tomoaki Nagasawa; Hiroki Sato; Akiko Suzuki; Kei Endo; et al. (Adis, Springer Healthcare, 2024)
Abstract Background and Objective Durvalumab plus tremelimumab (Durva/Treme) has recently been approved as a first-line or later-line treatment for patients with unresectable hepatocellular carcinoma (u-HCC) in Japan. We assessed the real-world outcomes of Durva/Treme for u-HCC, with a focus on treatment efficacy and safety. Methods We retrospectively evaluated 22 patients with u-HCC treated with Durva/Treme at Iwate Medical University during the period from 2023 to 2024, with a comparison of the clinical outcomes between patients who received Durva/Treme as first-line and later-line treatments. We further evaluated changes in the modified albumin-bilirubin (mALBI) grade during treatment. Results There were 10 patients in the first-line group and 12 patients in the later-line treatment group. During the follow-up with a median duration of 7.6 months, the median progression-free survival (first-line versus later-line: 4.7 months versus 2.9 months, p = 0.85), the objective response rate (0.0% versus 16.7%, p = 0.48), the disease control rate (60.0% versus 58.4%, p = 1.00), and the incidence of any adverse event (50.0% versus 75.0%, p = 0.38) were not statistically different between the two groups. The changes in the mALBI scores were not statistically significant (p = 0.75). Conclusions Durva/Treme may be effective and safe for patients with u-HCC, even in patients who receive Durva/Treme as a later-line treatment.